Islamic Economic Redefinition and its Methodology Among Contemporary Thinkers - Abi Suar; Meirson Meirison; Zerly Nazar (Kawanua International Journal of Multicultural Studies, 2020)
Abstract: The Islamic economic crisis from an epistemological perspective has been going on in recent years, based on many Islamic economic figures' writings. Monzer Kahf argues about Islamic economics's definition that there is no agreement among Muslim economists about the definition of Islamic economics, its scope, its relation to conventional economics, analytical methods and instruments, and even some of its basic assumptions. They view that the Islamic economy epistemologically still needs to be studied, while this Study, which has been going on for 40 years, seems to be running in place. In this Study, researchers used a library research method. This aims to reveal the redefinition of Islamic economics from contemporary economists, the methodological crisis that has hit Islamic economics, and the urgency of developing Islamic economics methodology among contemporary thinkers. The essence of the urgency of developing methodologies and approaches in Islamic economics is tawhid. The central or core concept that permeates all aspects of the epistemology of Islamic economics is tawhid. Tawhîd is the essence of Islam; tawhîd is considered the unity of knowledge and can be broken down into sources, methods and scientific knowledge. Knowledge comes from Allah's revelations to His Prophet, and reasoning, perception, and empiricism. Because of al-Attas, God's first type of knowledge is through direct revelation. The second is through the speculation of rational investigations based on his experience of the plausible and understandable.